Effects of Nitrogen Addition on Potential Soil Nitrogen-Cycling Processes in a Temperate Forest Ecosystem. Issue 1 (January 2016) - Sun, Jianfei; Peng, Bo; Li, Wei; Qu, Guifang; Dai, Weiwei; Dai, Guanhua; Jiang, Ping; Han, Shijie; Bai, Edith
Abstract : Abstract: Anthropogenic nitrogen (N) deposition substantially alters N cycling in terrestrial ecosystems because of its effects on soil physicochemical properties and soil microbes. Responses of N transformation processes to consecutive N additions are unclear, pointing to a lack of systematic understanding of N cycling under long-term N addition. This work combines 15 N tracing laboratory incubation with the FLUAZ model to study potential gross N-cycling processes in a temperate forest ecosystem in eastern Asia after 6 years of consecutive N additions at a rate of 50 kg N ha −1 year −1 . Soils from plots that received N additions had greater gross N mineralization probably because of higher soil carbon (C) and N than soils from control plots. Gross nitrification in soil from plots receiving N additions was inhibited likely because of lower pH in these plots. Higher NH4 + concentrations under N addition increased N immobilization by microbes, but NO3 − immobilization was much lower than NH4 + immobilization. Our results also show that N remineralization was stimulated by N addition and that microbes in N addition plots had greater N uptake probably because they adapted to high N concentration that led to accelerated microbial N turnover rate. This research highlights the importance of considering the effects of increasing N deposition on N processes mediated by microbes.